Growth of zinc oxide porous films via electrochemical anodization using glycerol based electrolyte - Beedri, Niyamat; Inamdar, Yusuf; Anjum Sayyed, Suhail; Shaikh, Arif; Jadkar, Sandesh; Pathan, Habib (Publishing House of Lviv Polytechnic National University, 2014)
ZnO porous films were successfully anodized on pure Zn sheet via electrochemical anodization in the glycerol base electrolyte containing ammonium fluoride salt as a pore enhancing agent. The structural and morphological properties of anodized and annealed films were characterized by X-ray diffraction and scanning electron microscopy, respectively. This shows the formation and growth of ZnO porous structure. На чистому цинковому листі, за допомогою електрохімічного анодування в електроліті на основі гліцерину, що містить фторид амонію як засіб для підсилення пор, анодовано пористі плівки ZnO. Структурні та морфологічні властивості анодованих і відпалених плівок визначено рентгенівською дифракцією та скануючою електронною мікроскопією, відповідно. Встановлено утворення та зростання пористої структури ZnO.
Приріст пористих плівок оксиду цинку за допомогою електрохімічного анодування з використанням електроліту на основі гліцерину
Keywords: anodization; zinc oxide; porous; annealed film; анодування; оксид цинку; пористий; відпалена плівка